Income and distribution effects of migration and remittances: an analysis based on CGE models for selected CIS countries - Aziz Atamanov; Matthias Luecke; Toman Omar Mahmoud; Roman Mogilevsky; Kseniya Tereshchenko; Natalia A. Tourdyeva; Ainura Uzagalieva; Vitaly Vavryschuk (Center for Social and Economic Research (CASE), 2009)
This paper analyzes the direct and indirect income effects of international labor migration and remittances in selected CIS countries. The analysis is based on computable general equilibrium (CGE) models for Moldova, Ukraine, Georgia, Kyrgyzstan, and Russia. All net emigration countries would experience a sharp contraction of private consumption in the absence of remittances. In Russia, the main effect of immigration has been to hold down the real wage (as potential capital stock adjustments in response to immigration are not reflected in our comparative-static modeling framework). The paper concludes that because of the important contribution of migration and remittances to stabilizing and sustaining incomes in many CIS countries, enhanced opportunities for legal labor migration should figure prominently in any deepening of bilateral relations between CIS countries and the European Union under the European Neighborhood Policy.
Keywords: C68; F22; F24; 330; CIS countries; labor migration; CGE model; system transformation